El municipio de Quito ante la campaña de Pasto. Transiciones entre Antiguo Régimen y republicanismo, 1822-1823 (Dossier: El momento colombiano de las repúblicas andinas. Desde el concepto de Colombia hasta el reconocimiento internacional) - Cabrera Hanna, Santiago (2021)
The present article explores the reaction of Quito’s town council to the Pasto campaign in the early years of the incorporation of the province of Quito into the Republic of Colombia. Establishment of a republican order based on the rule of law superseded preexisting municipal sovereignty based on tradition, customary laws, and the exercise of judicial justice. The use of special powers as provided for in the Constitution of Cúcuta to govern territories at war led to disputes between the departmental governor Vicente Aguirre and the town council for use of its revenues and the levy of compulsory contributions.